Improving Undergraduate Science Education Students’ Argumentation Skills through Debates on Socioscientific Issues (Jurnal Pendidikan IPA Indonesia, 2021)
This research aims to examine undergraduate students’ argumentation skills during and after the learning process in the classroom setting and their responses toward the implementation of socioscientific issues (SSI) through debate in the learning process. This research involved 32 undergraduate students and implemented design-based research with pretest and posttest in a natural classroom setting using three topics of SSI debate that widely discussed in Indonesia: Nuclear Powerplant (Topic 1), Food Preservation (Topic 2), and Genetically Modified Organism (Topic 3). Data was collected using observation sheets, tests, and questionnaires. Observation is to measure argumentation ability when applying the debate method in class settings, the test measures the improvement of argumentation skills, and questionnaires measure students’ responses to the application of the debate method. In this study, argumentation scores were obtained from six indicators and divided by a maximum score of 24 times 100. Normalized gain (N-gain) was calculated to determine the effectiveness of the intervention in the classroom. T-test was also conducted to test the significance of the differences in the pretest and posttest results on argumentation skills.  The results obtained in this study are: the argumentation skills score during the learning process for six groups were 95, 80.6, 90.3, 95, 83.3, and 77.5; the mean score of pretest and posttest were 52.22 ± 6.62 and 85.78 ± 4.72. The consistency of opinions shows the change from “agree” to “disagree” for Topics 1 and 3. The undergraduate students agree and consistently agree toward Topic 2. The paired t-test result also shows that the intervention statistically has a significant difference between the two means, indicating that the undergraduate students’ argumentation skills are better than before the intervention. Otherwise, most of the undergraduate students respond positively toward the implementation of the debate related to SSI. Despite some limitations, the debate on SSI can improve argumentation skills in classroom settings, especially in science education majors.